Results of a non-interventional multicenter observational study on the diagnosis and treatment of patients with axial psoriatic arthritis in rea-world clinical practice in the Russian Federation (NiSaXPA) - T. V. Korotaeva; E. E. Gubar; E. Yu. Loginova; Yu. L. Korsakova; E. A. Vasilenko; I.-D. Yu. Ilyevsky; L. V. Ivanova; E. Yu. Akulinushkina; P. А. Shesternya; O. V. Matveychuk; Yu. Yu. Grabovetskaya; A. A. Barakat; et al. (Современная ревматология, 2024)
Objective: The aim of the NiSaXPA study is to evaluate the quality of diagnosing, socio-demographic characteristics and treatment tactics of patients with axial psoriatic arthritis (axPsA) in real-world clinical practice in the Russian Federation.Material and methods. The study involved 600 patients from 21 clinical centers in the Russian Federation.Results and discussion. The diagnosis of axPsA was confirmed in 357 (59.5%) of 600 patients according to the centralized expert assessment. All 357 patients with axial lesions met criteria of the clinical guidelines for the treatment of patients with PsA. Of these, 201 (69%) patients had radiologically significant sacroiliitis (SI) according to Kellgren and 103 (59.2%) had active SI according to magnetic resonance imaging. The presence of syndesmophytes was confirmed in 119 (43.9%) patients. Inflammatory back pain was observed in approximately 80% of patients, most commonly in the lumbar and cervical spine. "Silent" sacroiliitis were found in 1.1–3.5 % of cases. 26.8% of patients were positive for HLA-B27. In the 6 months prior to the study, high PsA activity was present in 21.6% of patients according to the rheumatologist's assessment, while high activity according to the BASDAI index was found in 71.9 % of patients, and moderate and high activity according to the DAPSA index – in 82.7%. On the 24th week of observation, the number of patients with low activity according to BASDAI doubled and reached 66.3 %, while low activity and remission according to the DAPSA index amounted to 52.5% and 8.1% of patients, respectively. In most cases (about 27%), patients with axial manifestations were prescribed interleukin (IL) 17A inhibitors, about 14% of patients received tumor necrosis factor-α inhibitors, and about 4% received IL23 inhibitors.Conclusion. In 40.5% of patients, axial skeletal involvement in PsA was over-diagnosed due to misinterpretation of clinical and imaging data. The vast majority of patients (77%) were treated with synthetic disease-modifying antirheumatic drugs, mainly methotrexate, which do not affect the activity of spondylitis. Biologic disease-modifying antirheumatic drugs (bDMARDs) were taken by 46.5% of patients. Switching therapy to bDMARDs led to a significant reduction in disease activity.In order to improve the quality of medical care, the Russian clinical guidelines for the treatment of patients with PsA and the algorithms for the diagnosis of axial involvement need to be comprehensively implemented.